Cardioprotection by limb remote ischemic preconditioning in rats: discrepancy between meta-analysis and a three-center in vivo study. (10th June 2022) - Sayour, N; Brenner, GB; Makkos, A; Kovacshazi, CS; Gergely, TG; Tian, H; Zenkl, V; Bencsik, P; Heinen, A; Schulz, R; Baxter, GF; Zuurbier, CJ; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Heart Program funded by the National Research, Development and Innovation Office of Hungary Higher Education Institutional Excellence Programme of the Ministry of Human Capacities in Hungary, within the framework of the Therapeutic development thematic programme of the Semmelweis University Purpose and aims: Despite promising preclinical results on cardioprotection by remote ischemic preconditioning (RIPC), large-scale clinical trials show no reduction in infarct size (IS). This translational gap might be due to unknown confounding factors and lack of sufficient high-quality in vivo preclinical proof-of-concept studies. Therefore, here we performed randomized, blinded in vivo studies in three study centers using the most often reported methodological settings, as well as a systematic review and meta-analysis of RIPC studies. Methods and Results: Male Wistar rats were subjected to 20 to 45 min cardiac ischemia followed by 120 min reperfusion with or without preceding RIPC by 3 or 4×5-5 min occlusion/reperfusion of one or two femoral vessels by clamping, tourniquet, or pressure cuff. RIPC did not reduce IS, microvascular obstruction, or arrhythmias at any study centers. Systematic review and meta-analysis focusing on in vivo rat models of myocardial ischemia/reperfusion injury with limb RIPC showed that RIPC reduces IS by 21% on average; however, a tendency for publication bias towards positive results was found. In addition, our systematic review showed methodological heterogeneity and insufficient reporting quality in a high proportion of studies. Conclusion: We report for the first time the lack of cardioprotection by RIPC in rats, assessed in individually randomized, blinded in vivo studies, involving multiple study centers. Although unanimously showing cardioprotection by RIPC, the majority of reviewed studies were inadequately reported, and under-publication of neutral studies is plausible. Methodological confounding factors leading to the discrepancy between meta-analysis and the present studies cannot be identified; insufficient reporting quality, heterogeneity of the applied settings, and selection bias against studies with neutral outcome may contribute to this discrepancy. More preclinical studies with adequate quality control, together with publication of neutral studies, are required to support development of clinically translatable cardioprotective interventions.